Sodium selenate as a therapeutic for tauopathies: A hypothesis paper - Dilcher, Roxane; Malpas, Charles B.; Walterfang, Mark; Velakoulis, Dennis; O’Brien, Terence J.; Vivash, Lucy (Frontiers in Aging Neuroscience, 2022)
In a large proportion of individuals with fronto-temporal lobar degeneration (FTLD), the underlying pathology is associated with the misfolding and aggregation of the microtubule associated protein tau (FTLD-tau). With disease progression, widespread protein accumulation throughout cortical and subcortical brain regions may be responsible for neurodegeneration. One of the syndromes of FTLD is the behavioral variant of frontotemporal dementia (bvFTD), in which the underlying pathology is heterogenous, with half of the cases being related to FTLD-tau. Currently, there are no approved disease-modifying treatments for FTLD-tau, therefore representing a major unmet therapeutic need. These descriptive, preliminary findings of the phase 1 open-label trial provide data to support the potential of sodium selenate to halt the cognitive and behavioral decline, as well as to reduce tau levels in a small group of participants with bvFTD (N = 11). All participants were treated with sodium selenate over a period of 52 weeks. Cognition was assessed with the Neuropsychiatry Unit Cognitive Assessment Tool (NUCOG, total scores), social cognition with the Revised Self-Monitoring Scale (RSMS, total scores), behavior with the Cambridge Behavioral Inventory (CBI), and carer burden with the Caregiver Buden Scale (CBS). Fluid biomarker measures include cerebrospinal fluid of total tau (t-tau), phosphorylated tau (p-tau181), NfL, p-tau181/t-tau, t-tau/Aβ1–42, and p-tau181/Aβ1–42 levels. After treatment at follow-up, cognition and behavior showed further negative change (based on a reliable change criterion cut-off of annual NUCOG decline) in the “progressors,” but not in the “non-progressors.” “Non-progressors” also showed elevated baseline CSF tau levels and no increase after treatment, indicating underlying tau pathology and a positive response to sodium selenate treatment. Significant changes in MRI were not observed. The findings provide useful information for future clinical trials to systematically assess the disease-modifying treatment effects of sodium selenate in randomized controlled designs for bvFTD and FTLD-tau pathologies.